Water conservation for small- and medium-sized utilities - Green, Deborah, 1950- (American Water Works Association, 2010)
Annotation For utilities serving up to 100,000 customers, this book provides guidance on implementing a water conservation program. With a menu of conservation approaches from which to choose, the book lets utilities plan a custom program. Includes worksheets, cost analysis, sample programs, and recommended budgets.
Keywords: Water conservation.; elektronické knihy; electronic books